Actual ineficiente gestión micro curricular en el proceso de enseñanza aprendizaje de los y las docentes de la unidad educativa SAINT DOMINIC SCHOOL durante el año lectivo 2016-2017. Diseño de un manual de gestión. - Núñez Almeida, Maribel Verónica (2018)
This research work shows the reality found in the "Saint Dominic School" Educational Unit, which presents an inefficient micro-curricular management, which affects the quality of the teaching-learning process of the institution's teachers. The objective of the project is to organize and establish the development of micro-curricular planning in the various areas, it is supported by a theoretical basis, identifying through the application of interviews with managers and surveys of teachers and students about the difficulties of the staff. teacher in the planning process. The applied methodology was descriptive and feasible project type; allowing the information obtained to determine the current situation of the problem, using the dialectical and analytical methods to establish the aspects considered weak and on which didactic strategies, formats and evaluation instruments were designed, as well as the elaboration of a management and planning manual micro curricular in accordance with the new curricular model of the country, all with the purpose of contributing to develop the professional teaching level in the planning process.